Poly-L-lysine functionalized large pore cubic mesostructured silica nanoparticles as biocompatible carriers for gene delivery - Hartono, S.; Gu, W.; Kleitz, F.; Liu, Jian; He, L.; Middelberg, A.; Yu, C.; Lu, G.; Qiao, S. (2012)
Large pore mesoporous silica nanoparticles (LP-MSNs) functionalized with poly-l-lysine (PLL) were designed as a new carrier material for gene delivery applications. The synthesized LP-MSNs are 100-200 nm in diameter and are composed of cage-like pores organized in a cubic mesostructure. The size of the cavities is about 28 nm with an entrance size of 13.4 nm. Successful grafting of PLL onto the silica surface through covalent immobilization was confirmed by X-ray photoelectron spectroscopy, solid-state 13C magic-angle spinning nuclear magnetic resonance, Fourier transformed infrared, and thermogravimetric analysis. As a result of the particle modification with PLL, a significant increase of the nanoparticle binding capacity for oligo-DNAs was observed compared to the native unmodified silica particles. Consequently, PLL-functionalized nanoparticles exhibited a strong ability to deliver oligo DNA-Cy3 (a model for siRNA) to Hela cells. Furthermore, PLL-functionalized nanoparticles were proven to be superior as gene carriers compared to amino-functionalized nanoparticles and the native nanoparticles. The system was tested to deliver functional siRNA against minibrain-related kinase and polo-like kinase 1 in osteosarcoma cancer cells. Here, the functionalized particles demonstrated great potential for efficient gene transfer into cancer cells as a decrease of the cellular viability of the osteosarcoma cancer cells was induced. Moreover, the PLL-modified silica nanoparticles also exhibit a high biocompatibility, with low cytotoxicity observed up to 100 µg/mL. © 2012 American Chemical Society.